Triiodo-L-Thyronine Promotes the Maturation of Cardiomyocytes Derived From Rat Bone Marrow Mesenchymal Stem Cells. Issue 5 (May 2016) - Shi, Shu-tian; Wu, Xing-xin; Hao, Wen; Wang, Xiao; Miao, Huang-tai; Zhen, Lei; Nie, Shao-ping
Abstract : Abstract: Bone marrow mesenchymal stem cells (BMMSCs) can differentiate into cardiomyocytes and be used in cardiac tissue engineering for heart regeneration. However, the effective clinical application of cardiomyocytes derived from BMMSCs is limited because of their immature phenotype. The aim of this study was to investigate the potential of triiodo-L-thyronine (T3) to drive cardiomyocytes derived from BMMSCs to a more mature state. BMMSCs were divided into 3 groups: untreated controls, differentiated, and T3 treated. The differentiation potential was evaluated by immunofluorescence microscopy and flow cytometry. Data were represented as the numbers of cells positive for the troponin I (cTnI), α-actinin, GATA4, and the connexin-43 (Cx-43). The mRNA levels of these specific markers of cardiomyocytes were determined by quantitative real-time polymerase chain reaction. The levels of cardiomyocytes markers protein and octamer-binding transcription factor 4 (Oct-4) were determined by Western blot analyses. Our data demonstrate that T3 treatment leads to a significant increase in cells positive for cTnI, GATA4, Cx-43, and α-actinin. The mRNA and protein expression levels of these specific markers of cardiomyocytes were also increased after T3 treatment. At the same time, the protein expression level of Oct-4 was substantially downregulated in T3-treated cells. These results demonstrate that T3 treatment increases the differentiation of BMMSCs induced to cardiomyocytes and promotes their maturation.